Young people's drug use stayed level during pandemic. Issue 34 (27th August 2021) - Knopf, Alison
Abstract : Alcohol use declined and use of nicotine and misuse of prescriptions increased among 10‐to‐14‐year‐olds during the pandemic, according to a study published last week. Overall, the rate of drug use among these young people remained stable during the pandemic based on repeated surveys of more than 7, 800 people ages 10 to 14 conducted between September 2019 and August 2020.